Magnetic Resonance Elastography of the Heart - Elgeti, Thomas; Sack, Ingolf (Current Cardiovascular Imaging Reports, 2014)
Cardiac magnetic resonance (MR) elastography noninvasively provides mechanics-based image contrast. The measurement of mechanical parameters is otherwise possible only by palpation or invasive pressure measurement. Measurement of parameters of myocardial shear stiffness is considered to be diagnostically beneficial especially in patients with diastolic dysfunction due to diffuse myocardial disease. Initial results of several single-center studies in animals, healthy volunteers, and patients suggest that cardiac MR elastography is capable of measuring shear stiffness-related diagnostic parameters. The following article shortly reviews the two main approaches used for cardiac MR elastography and outlines the results of the studies performed so far. © 2014 Springer Science+Business Media New York.
CRIS-Team Scopus Importer:2022-08-03
Keywords: Cardiac MR elastography; Diastolic dysfunction; Heart; Myocardial shear modulus